PENGEMBANGAN MEDIA PERAN (POP UP BOOK PERATURAN) PADA PEMBEPENGEMBANGAN MEDIA PERAN (POP UP BOOK PERATURAN) PADA PEMBELAJARAN IPAS KELAS IV SDN KEBOMLATI TUBANPENGEMBANGAN MEDIA PERAN (POP UP BOOK PERATURAN) PADA PLAJARAN IPAS KELAS IV SDN KEBOMLATI TUBAN - Hindri Caesar Tiara Konjin; Novialita Angga Wiratama (Prodi PGSD Universitas PGRI Ronggolawe, 2023)
Abstract. This research was conducted to determine the process of developing the level of validity, practicality, and effectiveness. This type of research is development research that develops Pop Up Book learning media products in science learning on regulatory material. The subjects in this study were fourth grade students at SDN Kebomlati Tuban. Development is carried out using the ADDIE model which consists of 5 (five) stages analyze, design, develop, implement, evaluate. The data collection instruments used were material expert validation sheets, media experts, teacher and student response questionnaire sheets, and student test sheets in the form of evaluation questions. The data collection technique used is validity data analysis, practicality data analysis and effectiveness data analysis. The results showed that the ROLE media (Regulatory Pop Up Book) at the material validation stage had a yield of 92.5% and was stated to be very valid. Language validation obtained a percentage of 97.14% and was declared valid. Media validation obtained a percentage of 80% and was declared valid. The results of the practicality test from the user (teacher) got a percentage of 93.33% and was stated to be very practical. While the results of the effectiveness test from ROLE (Regulatory Pop Up Book) obtained a result of 80.83% and was declared effective. Based on this, it shows that the ROLE developed is valid, practical, and effective for use in the learning process